Connection Motivation Work Nurse With Accuracy Charging Documentation Care Nursing at Sundari Hospital Medan - Suherni; Heni Triana; Lilis Pijiati (International Journal of Public Health Excellence (IJPHE), 2022)
Accuracy in filling out nursing care documentation is important in nursing services, because it will provide legal protection for both the giver and the recipient. Nursing care will reflect the quality of nursing care. The accuracy of filling nursing care documentation is influenced by motivation. From the results of the study the standards of nursing care applied were taken from 30 patient statuses. Can be taken the result of 61.5%. Who performs the standard nursing care that is applied. This study aims to determine the relationship between the work motivation of nurses and the accuracy of documentation of nursing care in the living health care installation at the Sundari Hospital in Medan. This type of research is quantitative descriptive with a cross sectional approach. Samples for the motivation of nurses were taken from 4 living medical care units with a total sample of 30 respondents, and for the accuracy of filling out nursing care documentation, quota sampling was taken. Data was taken using a questionnaire, for the accuracy of filling out nursing care documentation using the ASAK instrument from the Ministry of Health 1997. To determine the relationship between two variables, the Product Moment Correlation Test was carried out with the results of rxy = 0.474 and p = 0.008, which means that there is a significant relationship between nurses' work motivation. with the accuracy of filling out nursing care documentation in the inpatient room at Sundari Hospital Medan.